A (des)informação dos gestores/as e professores/as em sexualidade e educação sexual-relato de uma experiência - Leão, Andreza Marques de Castro [UNESP] (My University, 2014)
The present study aimed to know the training and guidance for managers and teachers in sexuality, in order to ascertain whether there was a demand for a training course covering these topics. The participants of this study of the qualitative and quantitative nature were managers and teachers of a municipality in the state of São Paulo, Brazil, more precisely 40 professionals who were invited to participate in a study by answering a questionnaire with semi-enclosed 20 questions. The purpose of this instrument was to know their training and information on sexuality. In general, in various questions about the trajectory of these professionals, contained in the questionnaire, it was evident the lack of training in sexuality and related issues, denouncing the training demand in this area. Considering this, it was developed and implemented a training course on sexuality for these professionals, which was conceived to treat different subjects in order to instigate in them a rethinking about the importance of sex education in the school environment. The results obtained so far show the mobilization of them in order to implement the proposed sex education in the school where they are working. Anyway, we know that there is much to do considering contributing in training of sexuality education, but this initiative shows that it necessary to provide more opportunities for initial and continuing education for these professionals.

O presente estudo buscou conhecer a formação e informação dos gestores/as e professores/as em sexualidade, a fim de averiguar se havia uma demanda formativa por um curso abarcando estas temáticas. Participaram deste estudo, de cunho quali-quantitativo, gestores/as (diretores/as e vicediretores/as) e docentes de um município do interior do Estado de São Paulo, Brasil, mais precisamente 40 profissionais que foram convidados/as a participar de um estudo respondendo a um questionário semifechado contendo 20 questões. O intuito deste instrumento era conhecer a sua formação e informação em sexualidade. Em linhas gerais, em várias perguntas sobre a trajetória de formação destes/as profissionais, contidas no questionário, ficou evidente a falta de formação em sexualidade e seus assuntos correlatos, denunciando a demanda formativa nesta área. Pensando nisso, foi elaborado e implementado um curso de formação em sexualidade voltado a estes/as profissionais buscando tratar diferentes assuntos, de maneira a instigar o repensar acerca da importância da educação sexual no entorno escolar. Os resultados obtidos até então mostram a sua mobilização à proposta de educação sexual ser implementada na escola em que atuam. Enfim, sabese que há muito a fazer pensando em contribuir na formação dos/as docentes em sexualidade, mas esta iniciativa ilustra que é preciso um olhar mais cuidadoso à formação inicial e continuada que está sendo oportunizada.
Keywords: Teacher training; Sexuality; Sex education; Manager; Formação de professores/as; Sexualidade; Educação sexual; Gestores/as